Programlanabilir Kontrol Sistemleri - Şahin, Coşkun (Fen Bilimleri Enstitüsü, 1990)
Bu çalışmada; "Programlanabilir Kontrol Sistemler i-PKS" incelenmiş, piyasada kullanılan PKS'lerin tasarım prensip lerinden örnekler verilmiş ve bir örnek tasarım yapılmıştır, Yapılan tasarımın konuya getirdiği yenilik; hızlı, ge nişletilmiş, tümleşik sistemlerin kontrolü amacı ile geliş tirilmiş "Akıllı Çevre Birimleri" dir.

"Programmable controler systems-PCS" was researched in this draft» The PCS which is used in industry, design methods and general standarts were examed in addition it was check how it was worked. But it can be expected that it is impossible' to examined all part of detail of PCS because there are many type of PCS in industry» There for it has been studied an example of PCS» The specification of system which was expected. We tried to collect the princple of working of PCS' s.nd to get some new idea» The base of working principle was examed as complete and step by step» It was tried explain, then input/output (I/O) standart unit was investigated» It was suggested a control set and method of writting structure» It is consist of three simple per i p he rial unit and in tel 1 i gen t I/O unit which is used for control of the temperature and in these device are used for experiment» Two of the simple hardware unit has S byte input also one of them has 8 byte output» The intelligent I/O (I-I/O) unit was send several signal and got it from center unit and each signal were checked v Central system connected via to RS232 serial line of PC and all control was done from this PC» Central system connected to 1-1 /Q unit with RS485 multipoint serial communication line. When there was communication between PC and intelligent hardware the soeed was 4800 baud.. ' It can be connected in a way 32 intelligent I/O and buffer micropt-oceses with 1024 unit of 8 byte capacity of intelligent I'/0. Central system can write to simple unite as RAM. Simple unit can be determined with switch where is body of this unit. For this reason each unit can recognaise their parameters. The newness of this experiment is surrounding unit. Every unit specialised their individual task. When the base of the control parameters was given (temperature curve, speed etc.) all prooreses were seen. Only Control Parameters can be given with centeral intelligent surrounding unit, changing of the situation of the, system can be got from it. In this way can be used for controlling the large system and production line. On the other hand the intelligent hardware unit can be designed to the base unit. Another intelligent hardware system can be connected to the first one. It is possible to produce to control unit for being done something like that. It provides to control large capacity system from center. To design of the intelligent unit can be done a person who must be specialist at -this subject. VI i Only disadvantage of this method that is necessary to follow to the communication agreement. From the simple systems to the complicated systems can be controlled with it. For this purpose it is necessary to price of the devices. The standart which is used this system, is EIA RS-485. EIA RS-485 Line Standart The instruction sets of prothotype PCS. Group 1) Control instruction of relais. i) Relay input group a) Contact input b) Edge triggering input ii) Relay output group a) Relay activate b) Relay deactivate c) Relay activate. and latch d) Relay deactivate and latch vm iii) Relay xnpu~ /output qroup b) Relay ınverse and latch Group 2) Timer and counter control group: i) Timer coni-ol group a > De 1 ay eo ac t i vate ta) Delayed deactivate c) Delayed activate and latch d) Delayec deactivate and latch e? ) Timer -"~eset ii) Counter control group a. ) C o u n t. e r i n c r a s s b) Counter incrase and reload c) Counter reset Group 3) Data control groups i ) Load ii) Exchange -iii) Add iv) Sufastract v) Multiply vi ) Division vii) Compare Group 4) Logic control groups i) and" :-:; i i ) OR iii) NOT iv) EX OR v) S hi. ft left. vi) Shift right vdi) Coding viii) Encoding Group 5) Programme control The memory map and variable name of prothotype PCS, For relais. I PK ' OK TT X t t t t PK i Relay position OK r- Relay previous position T T ; L a t c h t y o e X i Unused For timers, T /D C/B C A/P P2 Pİ PO,PÖ ; Pre timer number s Active/Passive : Output 5 Delayed activate s Latch type % Unused 'Delayed deactivate For junters, y ¦ x i v i x ! y n ı y / n f a / h.......... ;. I l _j__ i >. _ s H/ r HCTXVZ '-.'ass ive ¦;e 1 oao type/ 'drop f: OU t DU t s Unused In addition it provides many facilities to connect PC unit and to the system» Also it gives many facilities for programma-Dİe capacity which is very important fo- user» Best wishes anyone who is researching at this subject flrS 'w:
Programmade controler systems
Thesis (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1990
Tez (M.Sc. ) -- İstanbul Technical University, Institute of Science and Technology, 1990
Keywords: Denetim sistemleri; Control systems